SIMILARITIES BETWEEN ARCHEAN HIGH MGO ECLOGITES AND PHANEROZOIC ARC-ECLOGITE CUMULATES AND THE ROLE OF ARCS IN ARCHEAN CONTINENT FORMATION - Horodyskyj U.N.; Lee C.-T.A.; Ducea M.N. (My University, 2007)
Some insights into the origin of cratonic mantle can be gained from "eclogite" (loosely defined here as an assemblage containing garnet and any pyroxene) xenoliths hosted in kimberlites erupted through Archean (~ 2.5-3.5 Gy) cratons. One subset of Archean eclogite xenoliths, the low MgO Archean xenoliths, is presently believed to represent metamorphosed fragments of ancient altered oceanic crust, leading to the suggestion that Archean cratons were built, at least in part, by the accretion of oceanic lithospheric segments. However, another Archean subset, the high MgO Archean eclogite xenoliths, have major and compatible trace-element (Ni and Cr) systematics similar to high MgO arc-eclogite xenoliths originating from the lithospheric root underlying the Sierra Nevada batholith in California, an example of a Phanerozoic arc. The Sierran high MgO arc-eclogites represent cumulates from hydrous basaltic magmas beneath a thick continental arc. The compositional similarities between the Archean and Sierran high MgO eclogites suggest that not only might the Archean high MgO eclogites have a cumulate origin, as has previously been suggested, but they may be arc-related. If so, Archean high MgO eclogites provide evidence from within the mantle roots of cratons that some form of arc magmatism contributed to the formation and evolution of Archean continents. © 2007 Elsevier B.V. All rights reserved.
Keywords: ARCHEAN; CRATON; ECLOGITE; GARNET PYROXENITE; SIERRA NEVADA; XENOLITH; Precambrian::Archean; Докембрий::Архей